RELIABILITY OF EC 155 B1 AIRCRAFT COMPONENTS USING UPPER CONTROL LIMIT (ALERT LEVEL) FORMULATION - Ali Mahroni (Institut Teknologi Dirgantara Adisutjipto, 2020)
Airport Rescue & Fire Fighting equipment at Adi Soemarmo International Airport, Operational Vehicle PKP-PK, the number of main vehicles is 3 units, and 6 supporting units meet the standard requirements that have been determined according to the PKP-PK category at Adi Soemarmo Airport, namely category 8. it has a Daily Checklist of operational equipment in each main vehicle and support vehicle. Supporting Facilities for Airport Rescue & Fire Fighting totaled 194 where required for category 8 was 167 but there were still some shortcomings of the equipment needed. This can be shown in the table, namely the types of hydraulic / electrical (or combination) portable rescue equipment, oxygen resuscitation, and thermal imaging cameras. There are 380 Supporting Reserve Facilities for Rescue & Fire Fighting where the minimum equipment required is 355 but there is a lack of equipment, namely Proximity suit, Resuscitator, Helmet, and Binocular equipment.